An investigation of teachers' self-reported and actual written feedback practices in Egyptian ESL Classes - Farag, Lidya Magdy Ibrahim (AUC Knowledge Fountain, 2014)
There have been ongoing investigations on whether providing corrective feedback on grammatical errors in L2 writing is effective or not since the debate first emerged between Truscott (1996) and Ferris (1999). Research has focused mainly on students' performances and preferences as well as teachers' perceptions and beliefs regarding error correction. However, limited research has compared teachers' actual practices to their self-reported practices. Therefore, this study focused on written feedback practices in a university context in Egypt, where the researcher investigated how teachers actually corrected grammatical errors as compared to what they reported in the survey. The major error correction strategies used in this study were related to two categories: comprehensiveness (comprehensive and selective correction) and explicitness (direct, indirect coded, and indirect un-coded correction). Data were gathered using three instruments: (1) a survey filled out by 65 teachers, (2) written feedback samples collected from 13 teachers, and (3) follow-up interviews conducted with seven teachers. The teachers who participated in this study work at The School of Continuing Education at The American University in Cairo. Teachers’ responses to the survey were compared to their actual practices in the feedback samples they provided. The results indicated that there were various differences between the teachers' actual and self-reported practices, such as over-reported, under-reported, or contrasting reported practices. The researcher conducted follow-up interviews to have an in-depth investigation of the reasons for the differences found. The study showed that teachers tended to over-report their comprehensiveness practices and under-report their explicitness practices. In addition, the reported practices showed that the majority prefer using comprehensive, selective, and indirect coded corrections, while they actually practiced comprehensive and direct corrections. Possible implications were discussed regarding ways to minimize the differences between teachers' self-reported and actual practices, as well as suggestions for providing effective corrective feedback to L2 students' writing.